STRATEGI EMPLOYEE RELATIONS UNTUK MENINGKATKAN KINERJA KARYAWAN DAN CITRA PADA PT ASDP INDONESIA FERRY (PERSERO) - ASWAN JAYA (JURNAL ILMIAH MAKSITEK, 2020)
PT ASDP Indonesia Ferry (Persero) is a state-owned company engaged in the field of sea transportation services. To maintain the existence and compete with other transportation services, it is necessary to provide optimal services to the community as ship service users must be satisfied with the services provided by making various efforts to improve the quality of service for ship service users through various strategies. One of them is an employee relations strategy to improve employee performance and company image, because employees are the spearhead of the company which has an important role for the progress of the company.This study aims to determine the program or employee relations activities organized by public relations to improve employee performance and the image of PT ASDP Indonesia Ferry (Persero), to see the strategy and planning of public relations and employee relations programs primarily to improve employee performance and corporate image, to find out media used and obstacles in implementing employee relations programs.The method used in this research is descriptive qualitative research, carried out by gathering factual information that describes the phenomena that exist, and then identified to get a description that can be evaluated. Data formulation by interviewing was conducted with sources, observations and literature studies.Based on the research conducted, it can be seen that the employee relations strategy that runs on PT ASDP Indonesia Ferry (Persero) is divided into programs consisting of various activities, including managing programs and developing quality human resources, employee welfare programs, cultural company socialization programs, programs achievement motivation, special programs, and internal communication media programs. The results of the study indicate that the employment relations strategy at PT ASDP Indonesia Ferry (Persero) has been considered to be quite successful because it provides a fairly good response from employees, received by employees and employees have been satisfied with various activities organized by public relations at PT ASDP Indonesia Ferry ( Persero). Public Relations PT ASDP Indonesia Ferry (Persero) plays a role in building and maintaining good relations and mutual understanding between the company and the public so as to create a positive image of the company. For this reason, employee relations must be well established to provide satisfying services to customers. The most important element in employee relations is employee communication.